Investigating The Role of Semantic Change in Slang Word on Instagram and Its Influence on Informal Spoken Languange in The Classroom - Lailatul Jannah; Dinar Vincy Yunitaka Bahrudin; Ina Daril Hanna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the types of semantic change in slang words on Instagram and examines how these changes are adopted and reflected in students’ informal spoken language in the classroom. This research employs a qualitative case study design involving third-semester students of the English Education Department at Universitas Islam Madura. The data were collected through observation, interviews, documentation, and students’ spoken performance during guided informal speaking activities. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that four types of semantic change are identified in Instagram slang, namely extension, narrowing, degeneration, and regeneration of meaning, with degeneration being the most dominant type. Furthermore, the results show that these semantically shifted slang words are actively adopted by students in their informal spoken language. Based on (Brown’s 2004) speaking aspects, the use of slang contributes positively to students’ fluency, vocabulary, and comprehension, as they are able to express ideas more naturally and understand contextual meanings effectively. However, limitations are still found in accuracy and pronunciation, particularly in grammatical structure and word formation. In addition, the study indicates that Instagram plays a significant role as a source of linguistic input that accelerates vocabulary development and influences students’ speaking behavior. The findings highlight that semantic change in digital environments not only affects lexical meaning but also shapes real-time language use in classroom interaction. In conclusion, this study confirms that Instagram slang functions as a dynamic linguistic resource that enhances informal communication while simultaneously presenting challenges in linguistic accuracy. Therefore, educators are encouraged to integrate awareness of digital language use into classroom practice to support balanced language development